2017
DOI: 10.5152/tud.2016.77603
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of the EORTC risk tables to predict outcomes in non-muscle-invasive bladder cancer in Turkish patients

Abstract: Objective: To evaluate the consistency of the results of patients who were treated for non-muscle-invasive bladder cancer (NMIBC) in our clinic with the European Organization for Research and Treatment of Cancer (EORTC) risk table.Material and methods: Data were retrospectively analyzed from 452 patients who had undergone transurethral resection of bladder tumor (TUR-BT) between the years 2002, and 2010 for primary or recurrent NMIBC. Our study had a retrospective design but based on prospective cohort study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
2
4
0
Order By: Relevance
“…The EORTC-GUCG risk system is one of the commonly used models to evaluate the prognosis of patients, with a high predictive efficiency. 30 In this study, pathological factors as tumor size, grade and T stage were the main risk factors affecting EORTC-GUCG score in patients with bladder cancer, which was consistent with the conclusions of Busato, 31 Cerbone 32 and other studies. Following patient stratification through the EORTC-GUCG risk scoring system, the results revealed statistically significant differences in RFS outcomes (p<0.05) among the different groups, suggesting the accuracy of our patient datasets.…”
Section: Discussionsupporting
confidence: 91%
“…The EORTC-GUCG risk system is one of the commonly used models to evaluate the prognosis of patients, with a high predictive efficiency. 30 In this study, pathological factors as tumor size, grade and T stage were the main risk factors affecting EORTC-GUCG score in patients with bladder cancer, which was consistent with the conclusions of Busato, 31 Cerbone 32 and other studies. Following patient stratification through the EORTC-GUCG risk scoring system, the results revealed statistically significant differences in RFS outcomes (p<0.05) among the different groups, suggesting the accuracy of our patient datasets.…”
Section: Discussionsupporting
confidence: 91%
“…When assessing the discrimination capability of predictive models, an AUC or c-index of less than 0.70 reflects poor performance [ 36 ]. In the present study, we found that Choi et al [ 14 ] reported an AUC of 0.894 for the CUETO scoring model and Killinç et al [ 21 ] reported a c-index of 0.817 for the EORTC scoring model for recurrence outcome. However, in most of the external validations included for these predictive models (13 studies) [ 5, 16, 17, 20, 21, 23, 25–27, 31–34 ], we found a poor discrimination capability (AUC or c-index under 0.7).…”
Section: Discussionsupporting
confidence: 57%
“…After screening, a full‐text review was performed for 201 articles. According to the inclusion criteria, we finally identified 72 studies comprising 28 139 patients eligible for the meta‐analysis [12–83]. The demographics of each included study are shown in Table 1 and Table S2.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 72 included studies, five included only Ta NMIBC patients [12–16], and 26 studies included only T1 NMIBC patients [17–42]. The other 41 studies included both Ta and T1 patients [43–83].…”
Section: Resultsmentioning
confidence: 99%